The Relationship between Reading Fluency Improvement and Brainwaves in Children with Autism Spectrum Disorders. International Journal of Academic Research in Progressive Education and Development - Noor Syuhada, Abdul Hakim; Nurul Hanim, Nasaruddin (HRMARS, 2024)
The purpose of this study is to determine the relationship between reading fluency improvement and brainwaves in children with Autism Spectrum Disorders when using yellow overlay. The sample in this study consisted of sixteen ASD children aged between nine and eleven years from Sarawak, Malaysia. A correlational research design was used in this study. Results from the Pearson correlation test found a strong positive relationship between reading fluency improvement and beta brainwaves (r = 0.707, p < 0.05) at the frontal lobe using a yellow overlay. In addition, the temporal lobe results for reading fluency improvement and beta brainwaves (r = 0.560, p < 0.05) showed a moderate positive relationship while using a yellow overlay. However, the correlation results for alpha brainwaves at the frontal and temporal lobes were not significant because p = 0.320 and p = 0.601, respectively. In conclusion, this study proved that yellow overlay has a positive significant relationship between reading fluency improvement and beta brainwaves at the frontal and temporal lobes.